A Reference Architecture for Data-Driven Intelligent Public Transportation Systems - Franca Rocco Di Torrepadula; Sergio Di Martino; Nicola Mazzocca; Paolo Sannino (IEEE Open Journal of Intelligent Transportation Systems)
Smart cities include complex ICT ecosystems, whose definition requires the cooperation of several software systems. Among them, Intelligent Public Transportation Systems (IPTS) aim to effectively exploit public transit resources. Still, adopting an IPTS is non-trivial. Off-the-shelf IPTS are often tied to specific technologies and, thus, not easy to integrate within existing software ecosystems. Moreover, despite IPTS introduce several peculiar issues, there is a lack of domain-specific reference architectures, which would significantly ease the work of practitioners. To fill this gap, starting from the experience gained with the Hitachi Rail company in deploying a large-scale IPTS, we identify a set of requirements for IPTS, and propose a domain-specific reference architecture, compliant with these requirements, whose primary objective is facilitating and standardizing the design of IPTS, by providing guidelines to IPTS designers. Consequently, it eases also the interoperability among different IPTSs. As an example of an IPTS obtainable from the architecture, we present a solution currently deployed by Hitachi in a major Italian city. Still, being independent from the specific considered urban scenario, the architecture can be easily instantiated in different cities with similar needs. Finally, we discuss some research challenges which should be further investigated in this domain.